Best practices for government agencies to publish data: lessons from COVID-19 - Bastian Herre, PhD; Lucas Rodés-Guirao, MEng; Edouard Mathieu, MA; Hannah Ritchie, PhD; Charlie Giattino, PhD; Joe Hasell, MSc; Saloni Dattani, PhD; Esteban Ortiz-Ospina, PhD; Max Roser, ProfPhD (Elsevier, 2024)
Summary: Without data, knowing how to respond to the COVID-19 pandemic would have been impossible. Data were crucial to understanding how the disease spread and which efforts successfully protected people. Yet, national agencies often did not publish their data in an optimal way, which made responding to the pandemic challenging. Therefore, learning from what went well and what did not for the future is crucial. Drawing on our first-hand experience of republishing COVID-19 data, we identify seven best practices for how to publish data in an optimal way: collect the data that are relevant; make them comparable; clearly document the data; share them frequently and promptly; publish data at a stable location; choose a reusable format; and license others to reuse the data. These best practices are straightforward, inexpensive, and achievable, with some countries already having implemented most of them during the COVID-19 pandemic. More government agencies following these best practices will enable others to access their data and address the world's public health challenges-including the next pandemic.